(untitled) - Watson, Mark (San Francisco, 2004)
Java Programming 10-Minute Solutions provides direct solutions to the thorny problems you're most likely to run up against in your work. Especially when a project entails new techniques or draws you into a realm outside your immediate expertise, potential headaches abound. With this book, a veteran Java programmer saves you both aggravation and—just as important—time.
Keywords: Java (Computer program language),Java ( ngôn ngữ chương trình máy tính )